Frequência de aglutininas anti-A e anti-B em doadores do grupo “O” do hemocentro de Cruz Alta - RS - Borghetti, Aline Noal (2012)
The use of hemocomponents from blood group "O" in transfusions among different blood groups may lead to transfusion reactions if the anti-A and anti-B agglutinins, present in the donor s serum / plasma, show high titers scores equal to or higher than 100. The transfusion reactions most reported with antibodies of high titers are caused by platelet concentrate, due to the presence of plasma in this hemocomponent. Considering the small number of studies on the anti-A and anti-B hemolysins and the importance of these antibodies in transfusion practice, the goal of this work was to verify the frequency of these hemolysins and their association to genre and Rh factor in 500 serum samples of type "O" registered donors at the Blood Center of Cruz Alta, RS. The results showed that the frequency of donor blood group "O" considered dangerous was 11.6% (58), and non-dangerous 88.4% (442). There was a predominance between the dangerous 50% (29) to reactive anti-A hemolysin , 37.9% (22) anti-B and 12.1% (7) for agglutinins anti-A and anti-B. Sampling of donors was not homogeneous regarding sex and not the type of blood factor, prevailing men 65% (325), Rh positive. There was no correlation between antibody screening Irregulars (PAI) with regular search antibody anti-A and anti-B. Also there was no assocation betwiin the prevalence in the variables gender, blood Rh factor anti anti-A and anti-B. It was noticed that the anti-A shows reaction under great in comparison with the anti-B thus both react in 100% of cases to1/16 however, the anti-Adecreas its percentage from1/128 whereas anti-B 1/32. The age prevalence of dangerous donors for anti-A was between 33 to 46 years, anti-B from 16 to 25 years and for both antibodies between 25 and 33 years. The results of this research can be used to measure the prevalence of these hemolysins and prevent risks of incompatible transfusion events, since in transfusion practice there is greater availability of group "O" donors and these are not classified as risk-donor "O" yet. Thus, in the search for excellence in transfusion practice and, above all, effectivenessly, it is essential to standardize the Regular Antibodies Research.